(untitled) (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2025)
File verification is a crucial initial stage in population administration services to ensure the validity of File verification is a crucial initial stage in civil registration services to ensure the validity of population data and prevent document falsification. This final project aims to describe the verification process for authenticity of civil registration service documents by the Malang City Population and Civil Registration Office (Dispendukcapil). This article uses a qualitative descriptive method with data collection techniques through observation, interviews, and literature studies during the internship. The results of the study indicate that the verification process carried out by the Malang City Population and Civil Registration Office is in accordance with applicable guidelines and SOPs, starting from manual file inspection, QR code scanning, verification using the Centralized SIAK, to document validation with the issuing agency if the document is not issued by the Malang City Population and Civil Registration Office. To encourage more effective, transparent, and accountable public services in accordance with the principles of good governance, the use of technology in the verification process, such as scanning QR codes on population documents, reflects the implementation of e-government in providing public services.